2013
DOI: 10.1021/jp403828y
|View full text |Cite
|
Sign up to set email alerts
|

Further Theoretical Evidence for Hydrogen-Assisted CO Dissociation on Ru(0001)

Abstract: Extensive calculations based on spin-polarized density functional theory were carried out to examine how CH x are formed from the dissociation of CO on Ru(0001) in the presence of hydrogen. Common pathways, such as the direct CO dissociation and H-assisted route leading to HCO or COH, including alternative routes that involve the formation of HCOH and CH2O, were examined. The reaction energy and barrier for each elementary step were calculated. The calculations show that the carbide mechanism is not the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Inderwildi and coworkers predict that hydrogen‐assisted dissociation predominates on flat Co(0001) and Ru(0001) . Later studies found similar results on other crystal surfaces . However, van Santen and coworkers found that direct dissociation predominated over corrugated Ru( 11true2¯1), consistent with experimental evidence for CO dissociation on corrugated Ru surfaces .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Inderwildi and coworkers predict that hydrogen‐assisted dissociation predominates on flat Co(0001) and Ru(0001) . Later studies found similar results on other crystal surfaces . However, van Santen and coworkers found that direct dissociation predominated over corrugated Ru( 11true2¯1), consistent with experimental evidence for CO dissociation on corrugated Ru surfaces .…”
Section: Introductionmentioning
confidence: 61%
“…[26] Later studies found similar results on other crystal surfaces. [27][28][29] However, van Santen and coworkers found that direct dissociation predominated over corrugated Ru (11 21), [30] consistent with experimental evidence for CO dissociation on corrugated Ru surfaces. [31][32][33] COH intermediates have also been proposed.…”
Section: Introductionmentioning
confidence: 70%
“…8−10 Theoretical evidence suggests that the latter process, that is, dissociation assisted by hydrogen, is the preferred one. 8,9,11 The short lifetime and low concentration of the intermediate species make their experimental identification difficult, 12,13 yet recent X-ray spectroscopy experiments have succeeded in identifying a CHO intermediate during CO hydrogenation. 14 Here, we study the coadsorption and interaction of CO and H at low temperatures to determine the structures formed and the potential role of H in CO dissociation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Extensive experimental and computational works can be found as for this topic. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Depending on the catalyst type, the surface structure and With this background, in this contribution we will conduct a comparative survey on direct and hydrogen-assisted CO dissociation over Ni(211) and Ni 3 Fe(211) via state-of-the-art DFT calculations. Both the AA and AB steps of Ni 3 Fe(211) will be considered herein in order to illuminate the performance difference deriving from the structure feature.…”
Section: Introductionmentioning
confidence: 99%